Continuous use of glycomacropeptide in the nutritional management of patients with phenylketonuria: a clinical perspective - Pena, MJ (2021)
Background In phenylketonuria (PKU), modified casein glycomacropeptide supplements (CGMP-AA) are used as an alternative to the traditional phenylalanine (Phe)-free L-amino acid supplements (L-AA). However, studies focusing on the long-term nutritional status of CGMP-AA are lacking. This retrospective study evaluated the long-term impact of CGMP-AA over a mean of 29 months in 11 patients with a mean age at CGMP-AA onset of 28 years (range 15-43) [8 females; 2 hyperphenylalaninaemia (HPA), 3 mild PKU, 3 classical PKU and 3 late-diagnosed]. Outcome measures included metabolic control, anthropometry, body composition and biochemical parameters. Results CGMP-AA, providing 66% of protein equivalent intake from protein substitute, was associated with no significant change in blood Phe with CGMP-AA compared with baseline (562 +/- 289 mu mol/L vs 628 +/- 317 mu mol/L; p = 0.065). In contrast, blood tyrosine significantly increased on CGMP-AA (52.0 +/- 19.2 mu mol/L vs 61.4 +/- 23.8 mu mol/L; p = 0.027). Conclusions Biochemical nutritional markers remained unchanged which is an encouraging finding in adults with PKU, many of whom are unable to maintain full adherence with nutritionally fortified protein substitutes. Longitudinal, prospective studies with larger sample sizes are necessary to fully understand the metabolic impact of using CGMP-AA in PKU.